The Many Faces of Christianism : The 'Russian World' in Europe - Grozdanov, Zoran; Johnson, Sophia; Kratochvíl, Petr; Tol, Marietta van der (Political and Public Theologies, 2025)
Is the Russian invasion of Ukraine a 'Holy War'? This book offers insights into the complex ideology of the Russki Mir or 'Russian World', which must be understood as Russian-shaped world order or peace - but above all, a claim to the sacred. The collected essays describe how Far Right politics in Europe and its resonances with the Russian World nod to the changing meaning of Christianism, defying and transforming the categories of religion and politics, and challenging common conceptions of the role of Christianity in European politics.